3D-printed optogenetic neural probe integrated with microfluidic tube for opsin/drug delivery - Revathi Sukesan; Mohsin Mohammed; Keonghwan Oh; Malvika Sharma; Dipesh Chaudhury; Sohmyung Ha (Scientific Reports)
Abstract Optogenetics, known for its precision in neural stimulation, is integral to behavioral research, enabling the study of neural circuits involved in decision-making, memory, social interaction, and movement. Traditional methodologies require two separate surgeries: the first to deliver a viral vector containing the opsin gene to the targeted brain region, and the second to implant an opto-probe for light stimulation. This dual-step process increases the risk of tissue damage and misalignment between the injection and implantation sites. In this study, we present a 3D-printed multimodal optogenetic neural probe that combines light delivery and fluid injection into a single device. By integrating a commercially available microfluidic tube with a 3D-printed opto-probe, the device offers rapid and customizable assembly for diverse applications. The probe was implanted in the subthalamic nucleus of mice, enabling viral vector delivery and device implantation in a single procedure. Following viral expression, behavioral experiments demonstrated that optical stimulation increased travel distance and velocity, confirming effective neuronal activation. Immunohistochemistry analysis revealed successful expression of Channelrhodopsin-2 (ChR2(H134R)) through mCherry labeling of neurons, reduced astrocytic (GFAP) and microglial (ED1) activation around the implantation site, and preserved neuronal populations as confirmed by NeuN staining. These results highlight the device’s biocompatibility, minimal inflammatory response, and suitability for long-term neural modulation, with potential applications in research and clinical settings.